Environmental Sociology Approach From A Social Risk Perspective - Nursinah, Andi; Suabey, Suningsih; Kadir, Erni; Asmi, A. Syamsinar; Purbanova, Reni; Henderika Litaay, Simona Christina; Pannyiwi, Rahmat (International Journal of Health Sciences, 2023)
Environmental problems are a problem for society and are problems that threaten the patterns of social organization that exist in society because environmental problems are human creations, so humans must also find a solution. Social risk is related to uncertainty. This uncertainty occurs due to the lack or unavailability of sufficient information about what will happen. The sociological perspective is part of environmental analysis and is very important because society and the environment cannot be separated. Humans are the worst environmental risk due to their inability to recognize environmental problems and their lack of effort to tackle them. However, humans are also the key to solving environmental problems. It is not impossible for humans to prepare for good environmental risk management from now on. Environmental problems are a reality that must be faced by all humans on earth today. For this reason, a critical analysis of the social risks to society is required. Based on a literature review, modernization through the mastery of technology and science has created a technocratic society where the risk of environmental damage becomes a disaster for mankind.